2019
DOI: 10.3390/met9050563
|View full text |Cite
|
Sign up to set email alerts
|

Research on AZ80 + 0.4%Ce (wt %) Ultra-Thin-Walled Tubes of Magnesium Alloys: The Forming Process, Microstructure Evolution and Mechanical Properties

Abstract: Ultra-thin-walled tubes of magnesium alloys have received more and more attention in producing precision components for medical devices. Therefore, thin-walled tubes with high quality are desperately needed. In this study, the process of multi-pass variable wall thickness extrusion was carried out on an AZ80 + 0.4%Ce Mg alloy with up to five passes—one-pass backward extrusion and four-pass extension—to fabricate the seamless thin-walled tube with an inside diameter of 6.0 mm and a wall thickness of 0.6 mm. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This provided more nucleation particles for dynamic recrystallization (DRX), which was helpful to grain refinement, and also improved the room‐temperature formability of AZ80 magnesium alloy. Yan et al [ 11 ] studied the multipass variable wall thickness extrusion process of AZ80 + 0.4%Ce magnesium alloy. The results showed that the hot extrusion deformation significantly refined the grain size at an appropriate temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This provided more nucleation particles for dynamic recrystallization (DRX), which was helpful to grain refinement, and also improved the room‐temperature formability of AZ80 magnesium alloy. Yan et al [ 11 ] studied the multipass variable wall thickness extrusion process of AZ80 + 0.4%Ce magnesium alloy. The results showed that the hot extrusion deformation significantly refined the grain size at an appropriate temperature.…”
Section: Introductionmentioning
confidence: 99%
“…By preparing Mg-Gd-x, Mg-Y-x ternary, or multiple alloy systems (x = Y [10][11][12], Sm [13,14], Nd [15], Zn [16][17][18], Ag [19][20][21], etc. ), most researchers studied the structure and precipitation sequence of rare earth strengthening phases [22], explored the mechanical properties and fracture modes of samples with different heat treatments [23], and investigated the strengthening mechanism of rare earth elements in magnesium alloys [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of different types of second phases were formed as consequence [24]. Taking Mg-Ce and Al-Ce binary alloys as examples, the second phases found by experimental methods included MgCe [37], Mg 2 Ce [38], Mg 3 Ce [39], Mg 12 Ce [40], Mg 17 Ce 2 [40], AlCe [41], Al 2 Ce [42], Al 3 Ce [43], Al 4 Ce [25], Al 11 Ce 3 [44], etc. Although transmission electron microscopy (TEM), electron probe micro analyzer (EPMA), X-ray diffraction (XRD), differential scanning calorimetry (DCS), energy dispersive spectroscopy (EDS), and other techniques were used to analyze the structure and properties of these phases, the information on the formation sequence and thermodynamic stability of the phases was still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium (Mg) and its alloys, which have the advantages of a low density, a high specific strength, easy recyclability, etc., have broad application prospects in national defense, aerospace, automobile, and 3C communication [1][2][3][4]. However, due to their poor strength and low ductility at room temperature, the development and application of Mg alloys are still limited [5].…”
Section: Introductionmentioning
confidence: 99%